Skin traction and placebo effect in the preoperative pain control of patients with collum and intertrochanteric femur fractures - (:unkn) unknown (My University, 2010)
Background: Proximal femur fractures are one of the most common injuries necessitating operative treatment. The aim of this prospective study was to evaluate and compare the possible effects of the preoperative application of a skin traction device, with or without weights, on pain relief in patients with acute proximal femur fracture. Materials and Methods: This study included 108 preoperative patients with hip fractures. The subjects were randomly divided into three groups, and the following treatments were administered: Group 1, skin traction with 2 kg of weights; Group 2, skin traction without weights; and Group 3, pillow placement under the affected limb. Results: Pain was assessed using the visual analog scale (VAS). No significant differences were observed in the scores of the three groups before the pain relief treatment. All three modes of treatment resulted in significant pain reduction in subjects. Patients treated without a weight-loaded skin traction kit had better pain relief compared to the other two groups; this outcome was statistically significant. Conclusion: This study indicates that pillow placement under an injured limb can be safely used instead of traction, which has no significant benefit. However, an external device, such as a skin traction kit without weight, may be used in patients with persistent pain; this external device may have an additive placebo effect, as was proven in this study.